#### Answer

$(2t - c)sin(t) + t^2cos(t)$

#### Work Step by Step

$y= ccos(t)+ t^2sin(t)$
$y'= -csin(t) + (2tsin(t) + t^2cos(t))$
$y' = 2tsin(t) - csin(t) + t^2cos(t)$
$y'= (2t -c)sin(t) + t^2cos(t)$

Published by
Cengage

ISBN 10:
1285740629

ISBN 13:
978-1-28574-062-1

$(2t - c)sin(t) + t^2cos(t)$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.